Vinaya-patrikā : saṭīka - Tulasīdāsa, 1532-1623 (SAMP early 20th-century Indian books project, 1949)
Text, with commentary, on Vinayapatrikā, Hindi devotional work, by Tulasīdāsa, 1532-1623, Hindi poet.